Hernia mesh infection treatment following the repair of abdominal wall hernias: A single-center experience - He, Linxiang; Wang, Xuehu; Fan, Gaoxiang; Zhao, Yu (Frontiers in Surgery, 2022)
Introduction The mesh-based repair of abdominal wall hernias is a commonly employed approach as it is easy to implement and associated with low rates of hernia recurrence. However, the occurrence of hernia mesh infections following such repair can be extremely serious, and no clinical consensus regarding the optimal treatment of such infections has been established. This study was thus developed to review the management of hernia mesh infection cases treated at our center, summarizing the demographic and clinical characteristics of affected patients and summarizing our associated therapeutic experiences. Methods Data pertaining to 64 cases of hernia mesh infections treated at our center were retrospectively reviewed. Data were obtained from patient medical records, including general situation, hernia type, prior hernia repair approaches, type of mesh, and postoperative condition. Other reviewed outcomes include bacteriological and imaging findings, as well as treatment outcomes. In cases where conservative management was not successful, the approach to mesh removal (laparoscopic vs. open) was made based on the primary surgical approach and the type of material used for the repair. Results In total, 42 patients underwent primary open inguinal hernioplasty (including plug repair, preperitoneal mesh repair, and Lichtenstein repair), while 11 patients underwent laparoscopic repair (9 transabdominal preperitoneal, TAPP and 2 totally extraperitoneal,TEP), and 11 patients with incisional hernias underwent the intraperitoneal onlay mesh (IPOM) procedure. Six patients exhibited mesh erosion of the internal organs. Of these patients, 38 underwent mesh removal via open debridement, while 9 underwent laparoscopic exploration and open debridement, and 1 underwent laparoscopic mesh removal. No patients exhibited serious postoperative sequelae, serious complications, or mortality after the treatment of mesh infections.One patient experienced postoperative infection recurrence following partial mesh removal, with the appearance of a small fistula. Hernias recurred in 2 patients following mesh removal, and 1 patient underwent repair via laparoscopic IPOM. Conclusions While conservative treatment can cure early mesh infections, there is nonetheless a risk that these infections will recur. In view of the variety of surgical intervention of abdominal wall hernias at present,treatment of mesh infection should be individualized. Our findings suggest that hernias repaired via the placement of mesh in the preperitoneal space can more readily contribute to internal organ erosion and late-onset infections, with open debridement often being unable to completely remove the mesh without causing collateral damage. Laparoscopic exploration is an effective and minimally invasive approach to detecting internal organ involvement and removing the infected hernia mesh from affected patients.